2023
DOI: 10.7759/cureus.34256
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Matrix Metalloproteinase-21 in Oral Squamous Cell Carcinoma

Abstract: IntroductionOral squamous cell carcinoma (OSCC) is one of the most common cancer with increasing morbidity and mortality due to regional invasion, metastasis, and secondary malignancy along with associated medical complications. The degradation of matrix metalloproteinases (MMPs) is essential for the progression of carcinoma, hence MMPs are implicated in cancer invasion and metastasis as a biomarker. ObjectiveThe primary objective of this study was to find the expression of MMP-21 between oral squamous cell ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…17 Many studies indicate that this anti-apoptotic protein is expressed in OSCC making it a prognostic indicator as well as an alternative option in chemoresistance cases in form of "Bcl-2 inhibition". 18 The presence of "Bcl-2 expression" has been shown to possess substantial predictive value for the response to chemotherapy. 19 This study aims to assess the "Bcl-2" immunoexpression in OSCC.…”
Section: Original Articlementioning
confidence: 99%
“…17 Many studies indicate that this anti-apoptotic protein is expressed in OSCC making it a prognostic indicator as well as an alternative option in chemoresistance cases in form of "Bcl-2 inhibition". 18 The presence of "Bcl-2 expression" has been shown to possess substantial predictive value for the response to chemotherapy. 19 This study aims to assess the "Bcl-2" immunoexpression in OSCC.…”
Section: Original Articlementioning
confidence: 99%
“…According to a recent review, the most promising salivary markers for OSCC diagnosis were MMP-1, MMP-3 and MMP-9, but larger studies are needed to confirm their clinical utility. 53 MMP-12 and MMP-21 have been demonstrated to play an essential role in tumor evolution and may be useful non-invasive early diagnostic tools for detecting OSCC, [54][55][56] as well as therapeutic interventions in the future. Zong-Yun and Feng 57 reported that downregulation of growth inhibitory factor 4 (ING4) could stimulate upregulation of hypoxiainducible factor-1α (HIF-1α) and MMP-14, promoting development, EMT, invasion and metastasis of OSCC, thus suggesting that these effectors could be used as significant prognostic markers.…”
Section: Functions Of Matrix Metalloproteinases and Their Endogenous ...mentioning
confidence: 99%